Fundamental studies on the grading of coniferous sawlogs for the production of structural and industrial lumber - Laurens, H. C.(Hugh Conrad) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1977.